The Lesotho Education Act of 1995/96, and its socio-economic and academic impact on Lesotho teachers: a case study in Maseru, Lesotho - Motaba, Mokomatsili Nathaniel Ndaba (My University, 2014)
This study examined how the Lesotho Education Act of 1995 was initiated, formulated and implemented. In addition, the study investigated teachers' perceptions of the impact of the Act on them. The study was conducted through stakeholder interviews, school visits and an examination of official documents, education reports and minutes of meetings. First, the study has established that the Act was initiated to phase out churches from school management in church schools, contrary to its stated objectives of promoting education. Second, the process of formulating and implementing the Act was bureaucratic and lacked coherence, sustainability and political consensus. Third, the Act has left teachers disillusioned and feeling disempowered by not accommodating their representation in structures dealing with their employment, conditions of service, promotion and demotion, transfer, discipline, dismissal, and designing the national curriculum. It has no provision for them to unionise, and does not even bind the employing authority to allow them to influence policies at national level. Fourth, on the provision of education, the Act is seemingly inconsistent with the national Constitution and other conventions on the Rights of Child and conventions which Lesotho signed. Contrary to them, the Act makes the provision of education in Lesotho circumstantial. Keywords: Lesotho Education Act 1995, Lesotho Education Stakeholders, Lesotho Church Education, Lesotho government and churches, Lesotho Teachers,
Keywords: Education and state--Lesotho; Education--Lesotho--History; Teachers--Lesotho